Praktik Goreng-Menggoreng Saham Di Indonesia Di Tinjau Dari Undang-Undang Nomor 8 Tahun 1995 Tentang Pasar Modal - Bahy Frederick J Eryansan; Waiwurin Safrianus; Stefanus Don Rade; Yustinus Pedo; Dwityas Witarti Rabawati (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The practice of investing using stock instruments often occurs the practice of frying stocks, which means manipulating the price of a stock that is actually illiquid so that it jumps above normal. This practice of frying stocks is carried out by market participants with the aim of certain interests. Market manipulation itself is a practice carried out by one and/or several parties to create a false stock market price, with the aim of making a profit. This research uses normative juridical research, namely by examining statutory products related to what the researcher wants to examine. Preventive protection is legal protection that is carried out with the aim of preventing fraudulent practices in the Capital Market that can lead to losses for investors, while repressive legal protection is when there are problems between financial service providers and their consumers, Bapenam-LK or OJK has the authority to provide defense or legal protection for the public as consumers, in this case investors. The preventive action also carried out by Bapenam-LK is to regulate that the securities prospectus is prohibited from containing misleading content or untrue information about material facts or presenting information about the advantages or disadvantages of the securities offered. The practice of stock frying is illegal and violates market regulations.Â